2003
DOI: 10.1081/clt-120022003
|View full text |Cite
|
Sign up to set email alerts
|

Dural Sinus Thrombosis with Severe Hypernatremia Developing in a Patient on Long-Term Lithium Therapy

Abstract: Dural sinus thrombosis has not been described in a patient with hypernatremia resulting from lithium-induced nephrogenic diabetes insipidus. A 63-year-old man on chronic lithium therapy for schizoaffective disorder was transferred to the Emergency Department with dehydration and signs of central nervous system dysfunction after a 3-week isolation in a room in a psychiatric hospital due to exacerbation of psychiatric disorder, during which he refused to eat. Laboratory examination revealed hypertonic hypernatre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…This association has been previously reported. [13][14][15] A comparison of therapeutic modalities was not feasible in this series because of the retrospective and nonrandomized study design. Several authors have advocated thrombolytic therapy.…”
Section: Discussionmentioning
confidence: 93%
“…This association has been previously reported. [13][14][15] A comparison of therapeutic modalities was not feasible in this series because of the retrospective and nonrandomized study design. Several authors have advocated thrombolytic therapy.…”
Section: Discussionmentioning
confidence: 93%
“…Although we identified DVTs after lithium toxicity, thrombosis has also been reported in patients with normal lithium concentrations. Kamijo et al [8] reported dural sinus 2…”
Section: Discussionmentioning
confidence: 99%
“…Wasay et al [ 7 ] reported superior sagittal sinus thrombosis associated with lithium-induced nephrogenic diabetes insipidus. Kamijo et al [ 8 ] reported a patient with dural sinus thrombosis and severe hypernatremia that had developed after long-term lithium therapy. DVTs associated with lithium toxicity have also been reported [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…We have found few cases documented and the mechanism of action is not known. In all references found the population studies are people with lithium treatment who develop symptoms of diabetes insipidus by the simultaneous presence of other pathologies: trauma (Olson, 2004), aortic stenosis (Hensen, 1997), cavernous sinus thrombosis (Kamijo, 2003). The role of lithium in the regulation of ADH release is discussed due to its participation in osmolarity and its action on osmoreceptors as controllers of ADH release (Gold, 1983 In our case it is appropriate to note the existence of viral encephalitis in the appearance of the picture, so it is worth recalling the pathological images of sella and pituitary findings.…”
Section: Discussionmentioning
confidence: 99%